Dopamine and pain sensitivity: neither sulpiride nor acute phenylalanine and tyrosine depletion have effects on thermal pain sensations in healthy volunteers. - Susanne Becker; Marta Ceko; Mytsumi Louis-Foster; Nathaniel M Elfassy; Marco Leyton; Yoram Shir; Petra Schweinhardt (PLoS ONE)
Based on animal studies and some indirect clinical evidence, dopamine has been suggested to have anti-nociceptive effects. Here, we investigated directly the effects of increased and decreased availability of extracellular dopamine on pain perception in healthy volunteers. In Study 1, participants ingested, in separate sessions, a placebo and a low dose of the centrally acting D2-receptor antagonist sulpiride, intended to increase synaptic dopamine via predominant pre-synaptic blockade. No effects were seen on thermal pain thresholds, tolerance, or temporal summation. Study 2 used the acute phenylalanine and tyrosine depletion (APTD) method to transiently decrease dopamine availability. In one session participants ingested a mixture that depletes the dopamine amino acid precursors, phenylalanine and tyrosine. In the other session they ingested a nutritionally balanced control mixture. APTD led to a small mood-lowering response following aversive thermal stimulation, but had no effects on the perception of cold, warm, or pain stimuli. In both studies the experimental manipulation of dopaminergic neurotransmission was successful as indicated by manipulation checks. The results contradict proposals that dopamine has direct anti-nociceptive effects in acute experimental pain. Based on dopamine's well-known role in reward processing, we hypothesize that also in the context of pain, dopamine acts on stimulus salience and might play a role in the initiation of avoidance behavior rather than having direct antinociceptive effects in acute experimental pain.